IMPLEMENTASI INTEGRASI SAINS DAN ISLAM DALAM KURIKULUM DI UNIVERSITAS SAINS AL-QUR’AN WONOSOBO - Linnaja, Ngatoillah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This study aims to analyze the implementation of the integration of science and Islam in the curriculum of Universitas Sains Al-Qur’an (UNSIQ) Wonosobo as an effort to address the dichotomy between secular and religious sciences that persists in Islamic education. Using a case study approach, this research examines the concept, methods of implementation, and challenges encountered in this integration. The findings reveal that UNSIQ’s concept of integration focuses on unifying worldly and spiritual knowledge through a harmonious approach between revelation and intellect. Its implementation is carried out through the development of an Islamic values-based curriculum applied across all courses, aiming to foster a comprehensive understanding for students in connecting scientific knowledge with religious values. However, this implementation faces several challenges, including curriculum dualism, limited understanding among lecturers, and insufficient policy and resource support. This study recommends strengthening university policies, adequate budget allocation, and enhancing lecturer competencies to ensure the effective and sustainable integration of science and Islam at UNSIQ.